Fafhrd and the Gray Mouser omnibus - Chaykin, Howard V.; O'Neil, Dennis, 1939-2020; Effinger, George Alec (Dark Horse Books, 2024)
"Fritz Leiber ranks among the giants of fantasy and science fiction visionaries, capturing multiple Hugo, Nebula, and World Fantasy Awards and influencing a generation of writers. And his most renowned creations are the swashbuckling Fafhrd and the Gray Mouser stories. Collected here are adaptations of some of the finest of these tales. Join the hulking barbarian and the diminutive rogue as they battle swordsmen, necromancers, and flagons of strong drink!"--